A checklist of the Kateretidae and Nitidulidae of Iran (Coleoptera: Cucujoidea) - Lasoń, Andrzej; Ghahari, Hassan (Zootaxa, 2013)
The current knowledge of the geographic distribution of short-winged flower beetles and sap beetles (Kateretidae and Nitidulidae, respectively) from Iran is summarized. In total, 84 species of Nitidulidae (in 22 genera and 5 subfamilies: Epuraeinae, Carpophilinae, Cryptarchinae, Nitidulinae, Meligethinae) and 6 species of Kateretidae (in 4 genera: Brachyleptus Motschulsky, Brachypterolus Grouvelle, Brachypterus Kugelann, Kateretes Herbst) are listed. Brachyleptus discolor Reitter, Brachypterus glaber (Newman) (both Kateretidae), Epuraea distincta (Grimmer), Soronia oblonga (Brisout), Lamiogethes bidens (Brisout), Lamiogethes medvedevi (Kirejtshuk), Sagittogethes devillei (Grouvelle) and Xerogethes rotundicollis (Brisout) (Nitidulidae) are new records for Iran.